Monitoring equity in vaccination coverage: A systematic analysis of demographic and health surveys from 45 Gavi-supported countries. Issue 6 (7th February 2017) - Arsenault, Catherine; Harper, Sam; Nandi, Arijit; Mendoza Rodríguez, José M.; Hansen, Peter M.; Johri, Mira
Highlights: We measured inequalities in child vaccination coverage in 45 low- and middle-income countries. We explored how different measurement approaches may affect estimates and country comparisons. Wealth, education and multidimensional poverty revealed the largest inequalities. The slope and relative indices of inequality produced more reliable country comparisons. Our findings have helped Gavi, the Vaccine Alliance refine its equity monitoring strategy. Abstract: Objectives: (1) To conduct a systematic analysis of inequalities in childhood vaccination coverage in Gavi-supported countries; (2) to comparatively assess alternative measurement approaches and how they may affect cross-country comparisons of the level of inequalities. Methods: Using the most recent Demographic and Health Surveys (2005–2014) in 45 Gavi-supported countries, we measured inequalities in vaccination coverage across seven dimensions of social stratification and of vulnerability to poor health outcomes. We quantified inequalities using pairwise comparisons (risk differences and ratios) and whole spectrum measures (slope and relative indices of inequality). To contrast measurement approaches, we pooled the estimates using random-effects meta-analyses, ranked countries by the magnitude of inequality and compared agreement in country ranks. Results: At the aggregate level, maternal education, multidimensional poverty, and wealth index poverty were the dimensions associated with the largest inequalities. In 36 out of 45 countries, inequalities were substantial, with a difference in coverage of 10 percentage points or more between the top and bottom of at least one of these social dimensions. Important inequalities by child sex, child malnutrition and urban/rural residence were also found in a smaller set of countries. The magnitude of inequality and ranking of countries differed across dimension and depending on the measure used. Pairwise comparisons could not be estimated in certain countries. The slope and relative indices of inequality were estimated in all countries and produced more stable country rankings, and should thus facilitate more reliable international comparisons. Conclusions: Inequalities in vaccination coverage persist in a large majority of Gavi-supported countries. Inequalities should be monitored across multiple dimensions of vulnerability. Using whole spectrum measures to quantify inequality across multiple ordered social groups has important advantages. We illustrate these findings using an equity dashboard designed to support decision-making in the Sustainable Development Goals period.